Smart, Precision or Digital Agriculture and Farming - Current State of Technology - Honc, Daniel; Merta, Jan (Springer Nature Switzerland AG, 2020)
Together with smart homes, cities and factories, energy hubs and self-driving cars the smart agriculture or farming could be a way how to increase yields and efficiency as well as improve the welfare of farm animals, grow high quality crops and preserve the natural resources. Smart, precision and digital agriculture and farming current state survey with the technical challenges, interesting applications and future prospects is the aim of the paper. Worldwide and UE view is presented and compared with the situation in the Czech Republic. Authors are seeking for used or at least potential agriculture and farming applications of soft computing methods like fuzzy logic, machine learning and evolutionary computa-tion.
Chytré, precizní nebo digitální zemědělství a hospodaření – aktuální stav technologie
Keywords: smart; precision; digital; agriculture; chytrý; precizní; digitální; zemědělství; hospodaření; soft computing; farming; soft computing